PENGARUH PEMBERIAN EDUKASI PERIKSA PAYUDARA SENDIRI (SADARI) TERHADAP PENINGKATAN PENGETAHUAN TENTANG SADARI PADA REMAJA PUTRI DI SMA NEGERI 3 KOTA BIMA TAHUN 2025 - Dian Apri Nelyanti Nelyanti; Amirul Kadafi; Sri Rahayu; Ainun Kurniati (Akademi Kebidanan Harapan Bunda Bima, 2026)
Background: Breast cancer is one of the leading causes of death among women worldwide, including in Indonesia. Early detection can be carried out through Breast Self-Examination (BSE). However, knowledge of BSE among adolescent girls remains low due to limited health education. Objective: This study aimed to analyze the effect of BSE education on improving knowledge among adolescent girls at SMA Negeri 3 Kota Bima in 2025. Methods: This study employed a quantitative quasi-experimental design using the Two-Group Pretest-Posttest approach. The population consisted of all female students in grades XI–XII (96 respondents), selected through total sampling. The instrument used was a BSE knowledge questionnaire comprising 20 Guttman-scale questions. Data were analyzed using the Mann-Whitney test. Result: The results showed that before the intervention, knowledge in the experimental group was categorized as good (55.9%), fair (41.2%), and poor (2.9%). After receiving education, all respondents in the experimental group (100%) reached the good knowledge category. The Mann-Whitney test indicated a significant difference between the experimental and control groups after the intervention, with p = 0.000 (p < 0.05). Conclusion: In conclusion, providing BSE education significantly improved the knowledge of adolescent girls. This finding highlights the importance of implementing reproductive health education programs in schools to increase awareness of early detection of breast cancer.